Determinants of Elderly Behavior Follow the Posyandu in the Working Area of Kebonsari Primary Healthcare Surabaya - Made Ariani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: Indonesia is ranked 4th in the World with the largest population in 2017 of 261,890,882 million. According to the 2017 Central Bureau of Statistics, the elderly population is 23.4 million (8.97%) of the Indonesian population. The habit of the elderly attending the Integrated Health Center (Posyandu) can have a good impact on the health of the elderly in the future. Objective: The aims of this study was to analyze the factors associated with the participation of the elderly following the Posyandu. Method: This study used Cross Sectional design with a sample of 210 respondents aged 45-59 years; 60-74 years; 75-84 years; and >84 years old. The technique used in sampling is simple random sampling with its independent variables namely intention, social support, information access, personal autonomy, and action situations in the elderly. The dependent variable is the activity of the elderly following the Posyandu. The data collection technique used primary data and secondary data. Data were analyzed by the chi square test through the SPSS application to see factors related to the activity of the elderly following the Posyandu. Result: From the results of the analysis, all independent variables showed a relationship between the independent variables on the activity of the elderly in attending the Elderly Posyandu (P<a (a = 0.05)). The P value for each variable, namely the intention P value= 0.015 (RP 3.619: 95% CI 1.599-8.188); social support P value =0.008 (RP 2.374: 95% CI 1.285-4.385); access to information P value= 0.007 (RP 2,714: 95%CI 1.356-5.429); personal autonomy P value= 0.012 (RP 2.876: 95% CI 1.316-6.289); and the action situation P value= 0.0001 (RP 5.575: 95% CI 2.913-10672). Elderly people with supportive action situations tend to actively participate in Posyandu 5 times greater than the elderly with non-supportive action situations. Conclusion: there is a significant relationship between intention, social support, information access, personal autonomy, and the situation of the elderly's actions towards the active participation of the elderly in the Posyandu.